The Dynamic Host Configuration Protocol Version 6 Security And Privacy Mechanism - Ibrahim, Ayman Khallel (2020)
Internet Protocol version 6 (IPv6) is the most recent IP version that aims to accommodate hundreds of thousands of unique IP addresses for devices in the network. In IPv6 network, Dynamic Host Configuration Protocol version IPv6 (DHCPv6) is used to allocate and distribute IPv6 addresses and network configuration parameters to DHCPv6 clients. However, the DHCPv6 protocol was developed without a proper security mechanism making it vulnerable to various threats, such as rogue DHCPv6 server attack and passive attack. Two well-known issues of DHCPv6 are lack of verification mechanism that allows attackers to inject fake network configuration parameters into the network undetected; and privacy concerns due to lack of protection of client information in transit. In order to address these issues, several mechanisms were proposed by researchers to provide authentication and privacy protection for DHCPv6. However, most mechanisms lack the method to distribute the server authentication credentials; and ignore the client's privacy issue. This thesis intends to address the above mentioned issues by proposing DHCPv6Sec mechanism. DHCPv6Sec was evaluated and compared to Secure-DHCPv6 mechanism in terms of rogue DHCPv6 server prevention capability, privacy protection, processing time, traffic overhead, communication time, and message size limitation. The experiment results showed that DHCPv6Sec is superior in all aspects measured. DHCPv6Sec reduced processing time by 57%, and 136% during obtain IPv6 address and processing of Reconfigure message, respectively, compared to Secure-DHCPv6 mechanism. More, DHCPv6Sec reduced configuration time by 27% compared to Secure-DHCPv6 mechanism.